Determination of Nursing Students 'Views on Graduate Education and Career Planning - Mehtap KAVURMACI; Mehtap TAN; Duygu ARIKAN; İdris YILDIZ (Atatürk University, 2021)
Aim: The aim of this study was to determine the views of nursing students towards graduate education and career planning. Methods: The universe of this descriptive, cross-sectional study consisted of 201 students who attended the fourth grade in a public nursing faculty in Erzurum in 2018-2019 academic year and accepted to participate in the study. In the collection of research data, the Questionnaire Form and Career Future Scale were used to determine the socio-demographic characteristics of the students and their knowledge about graduate education. The data obtained from the research were analyzed using descriptive tests in the SPSS 21 package program. Results: The average age of the students participating in the study is 22.22±1.20 years. 83.1% of the students are women, 74.6% are graduates of Anatolian High School and 77.1% of them think of getting a graduate education. However, most of the students do not have sufficient knowledge in the processes related to graduate education. Students' Career Future Scale scores; Career Compatibility: 38.86±6.71, Career Optimism: 37.99±5.86, Perceived Knowledge about job markets: 9.31±2.06, and scale total score: 86.16±12.19. Conclusion: As a result of the research, it was found out that most of the nursing students were considering graduate education but they did not apply to graduate education. It is determined that students do not have enough information and career prospect scale average of students is high.